Profile of childhood blindness and low vision in Yemen: a hospital-based study - Bamashmus, Mahfouth A.; Al-Akily, Saleh A. (World Health Organization, Regional Office for the Eastern Mediterranean, 2010)
A retrospective review of records determined the frequency and causes of low vision and blindness in all children aged <16 years attending an ophthalmic practice in Sana'a, Yemen between January and December 2001. Of the 1104 children studied, 45 [4.1%] were found to have bilateral blindness and 115 [10.4%] were unilaterally blind; 48 children [4.3%] were bilaterally visually impaired and 109 [9.9%] were unilaterally visually impaired. The main causes of bilateral blindness included cataract, glaucoma and retinal disorders. The most common causes of bilateral low vision included refractive errors, keratoconus and retinal disorders. These results provide a basis for planning blindness prevention programmes in Yemen